CO₂ Based Taxation on Cars Is Rising in Europe - Dominika Kalinowska; Kerim Keser; Uwe Kunert (Weekly Report, 2009)
In recent years, CO2 emissions have become the leading basis of assessment for car taxes in most European countries. In July 2009, with a view to pursuing climate policy goals, also Germany began using this factor to assess taxation on cars. The DIW Berlin has carried out a systematic and quantitative comparison of car taxation in Europe.1 The results reveal high tax rates in over ten countries that levy CO2 based tax components and significant differences across vehicle segments. Other observations are periodic adjustments of the assessment basis with regard to fuel-consumption benchmarks. The German reform of the annual vehicle tax (Kraftfahrzeugsteuer) in favour of assessment based on CO2 emissions is weak compared to other countries-too weak to create incentives to buy more fuel efficient vehicles. Moreover, the revision in July 2009 was introduced too late, given that the CO2 emissions of newly registered vehicles have been significantly decreasing since 2006 and given that the new EU directive on reducing the CO2 emissions of cars will directly impact car manufacturers effective 2012.
Keywords: H23; O38; Q52; R48; 330; Environmental taxes; Technological change: Government policy; transportation: regulatory policies